Strategi Komunikasi Pendamping PKH dalam Menyampaikan Modul Perlindungan Anak untuk Mencegah Penelantaran dan Eksploitasi Anak Bagi KPM PKH Kecamatan Nisam - Amiruddin, Teungku (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2024)
This study aims to explore the communication strategies employed by PKH facilitators in delivering the Child Protection Module, specifically in Session 12, focusing on the prevention of child neglect and exploitation in Nisam District, North Aceh Regency. The research is motivated by the critical role of PKH facilitators in educating Beneficiary Families (KPM) to raise awareness and understanding of child protection. The study applied a qualitative approach with a case study method. Data were collected through observations, in-depth interviews, and thematic analysis of the communication patterns used by PKH facilitators. The findings reveal that communication strategies based on participation, empathy, and contextual adaptation significantly enhance KPM’s understanding of child protection issues. Facilitators utilized visual media such as posters and illustrative storytelling while adopting simplified language relevant to the audience's daily life. Challenges like low literacy levels and limited time were effectively addressed through inclusive and dialogical approaches. The primary conclusion is that effective communication strategies focus not only on message content but also on delivery methods that reach the audience personally and contextually. This research contributes significantly to the development of social education programs by emphasizing the importance of adaptive and participatory communication approaches to create sustainable social impacts.